A Bibliometric Mapping on Maqasid Shariah in Islamic Perspective - Lia Fitria; Nabilatul Hija; Muhammad Arsyi; Shabrina Kasyifa Firdausi (Maqasid al-Shariah Review, 2022)
This research aims to find out how much research on maqasid sharia and its coverage based on journals published with the theme "Maqasid Sharia in Economic Context". This research uses various scientific journals as data sources. By using keywords to find publications in the Dimensions database with the phrase "Maqasid Shariah". There are 660 journal articles from that have been published which is in line with the topic. Trends in publication development were used to analyze information relating to the study's subject using the bibliometric-displaying software VOSviewer by using meta-analysis technique. There are several keywords that are classified into four clusters. In the first cluster there are 24 words that can be grouped into the theme "Application of Maqasid Sharia Principles in Modern Cases". In the second cluster there are 15 words that are grouped into the theme "Sustainability Economics in Covid-19 Pandemic and Maqasid Sharia". The third cluster has 12 words related to the theme "Wealth Protection in Islamic Perspective and Maqasid Shariah". The last is cluster four which consists of 10 words related to the theme "Islamic Banking and Maqasid Shariah".